Research on Vibration Reduction Characteristics of Continuum and Noncontinuum System on Coupling for High-Power Gear Transmission Based on Particle Damping Materials - Wangqiang Xiao; Zhanhao Xu; Sheng Wang; Shaowei Yu; Kai Qin; Dike Hu (Shock and Vibration)
High-power gears are widely used in various engineering fields. The gear transmission system is an extremely complex elastic system, which produces complex vibration under internal and external excitation. For the vibration and noise problems caused by transmission error, a discrete element and finite coupling method based on the particle filling rate is proposed. Firstly, the gear dynamic model was established, and the particle damper was installed in the gear to reduce the vibration of the gear. Secondly, through the coupling process, the contact force and contact position between the noncontinuous medium and the continuous medium were correctly transferred to the corresponding nodes of the finite element analysis model. Then, the equivalent displacement mapping of the contact loads’ node of the gear was realized, and the transformation of the local coordinate to the global coordinate was carried out. Finally, by combining theoretical analysis with experimental verification, the influence of the filling rate of damping particles on the vibration reduction effect of the gearbox under different working conditions was studied. The 2 mm tungsten particles were selected, and the particle damper had the best damping effect when the filling rate was 88%.